Agricultural phosphorus and water quality: sources, transport and management - Sharpley, Andrew; Gburek, William; Heathwaite, Louise (Agricultural Research Centre of Finland, 1998)
Veteen joutuvan fosforin määrä säätelee makeiden vesien rehevöitymistä. Maatalousvaltaiselta valuma-alueelta tulevan fosforin alkuperää selvitettiin maankäytöltään vaihtelevalla alueella Pennsylvaniassa, USA:ssa tutkimalla valuma-alueen hydrologiaa ja maan fosforipitoisuutta. Alueen 39,5 ha:sta 30 % oli metsää, 50 % peltoa ja 20 % laidunta. Mehlich-3 -menetelmällä määritetty maan fosforipitoisuus oli 7-788 mg kg-1. Metsäalueiden maan fosforipitoisuus oli pieni (<30 mg kg-1), laitumilla mitatut arvot vaihtelivat 100-200 mg kg-1 ja väkilannoitteita ja lantaa saaneilla vilja- ja soijapelloilla fosforipitoisuudet ylittivät usein 200 mg kg-1. Alle 60 metriä laskuojasta olevan maan fosforipitoisuus näytti säätelevän ojaveden fosforipitoisuutta enemmän kuin koko valuma-alueen maan fosforipitoisuus. Viljelytekniset vesiensuojelu-toimet tulisikin kohdentaa valuma-alueen tähän osaan, jolla on suurin vaikutus alueelta lähtevän valumaveden fosforipitoisuuteen. Maatalousmaalta tulevaa fosforikuormitusta voidaan säädellä rajoittamalla maahan lisättävän fosforin määrää ja vähentämällä eroosiota ja pintavaluntaa.

Freshwater eutrophication is usually controlled by inputs of phosphorus (P). To identify critical sources of P export from agricultural catchments we investigated hydrological and chemical factors controlling P export from a mixed land use (30% wooded, 50% cultivated, 20% pasture) 39.5-ha catchment in east-central Pennsylvania, USA. Mehlich-3 extractable soil P, determined on a 30-m grid over the catchment, ranged from 7 to 788 mg kg-1. Generally, soils in wooded areas had low Mehlich-3 P (<30 mg kg-1), grazed pasture had Mehlich-3 P values between 100 and 200 mg kg-1, and cropped fields receiving manure and fertiliser applications were in most cases above 200 mg kg-1. Average P concentrations for ten storms during 1996 decreased 50% downstream from segment 4 to segment 1 (catchment outlet). Flow-weighted streamflow P concentrations were more closely related to the near-stream (within 60 m) than whole catchment distribution of high-P soils. This suggests that near-stream surface runoff and soil P are controlling P export from the catchment. Remedial measures should be targeted to these critical P source areas in a catchment. Measures include source (fertiliser and manure application) and transport management (reduce surface runoff and erosion).
Keywords: maatalous; fosfori; vesistönkuormitus; animal manure; catchments; critical source areas; drainflow; erosion; fertiliser; leaching; macropores; nonpoint source pollution; remediation; surface runoff; subsurface flow